2016
DOI: 10.1016/j.jvs.2015.12.057
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes after open infrainguinal bypass in patients with scleroderma

Abstract: Long-term outcomes after open infrainguinal bypass surgery in scleroderma patients are significantly worse than those in nonscleroderma patients. Careful consideration of their inherently poor outcomes should be made when reaching a decision for revascularization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 25 publications
0
6
1
1
Order By: Relevance
“…10,21 The results from the renal transplantation patients under study are largely similar to those from other groups of high-risk patients, such as those with connective tissue disease. 22 These results fall short of those from a recent study of non-ESRD patients that revealed primary patency of 59% and secondary patency of 84% at 3 years. 23 Although this study does not compare outcomes between open bypass and endovascular therapy in these patients, the modest outcomes of open revascularization that we have shown suggest that some caution might be warranted before embarking on open bypass surgery, especially for claudicants.…”
Section: Journal Of Vascular Surgerycontrasting
confidence: 80%
“…10,21 The results from the renal transplantation patients under study are largely similar to those from other groups of high-risk patients, such as those with connective tissue disease. 22 These results fall short of those from a recent study of non-ESRD patients that revealed primary patency of 59% and secondary patency of 84% at 3 years. 23 Although this study does not compare outcomes between open bypass and endovascular therapy in these patients, the modest outcomes of open revascularization that we have shown suggest that some caution might be warranted before embarking on open bypass surgery, especially for claudicants.…”
Section: Journal Of Vascular Surgerycontrasting
confidence: 80%
“…5,15,16,18 The outcomes from this study are similar to those from a study of patients with connective tissue diseases, who are also considered high risk for poor outcomes after IBS. 25 These findings demonstrate that Hispanics experience similar graft failure and limb salvage outcomes as white patients do within the HD-dependent population. Previous studies comparing outcomes of Hispanic patients in the general population have been conflicting.…”
Section: Discussionmentioning
confidence: 64%
“…The low primary, primary assisted, and secondary patency rates for both autogenous and prosthetic bypass conduits in this study relative to non-HD patients are in tandem with those from other high-risk groups. 18,19 Race and gender have been described as acting synergistically; black women, compared with white men as reference, have higher rates of early graft failure. 10,20 Data from the Project of Ex-Vivo vein graft Engineering via Transfection III (PREVENT III) multicenter trial suggest that black women may have smaller, less suitable veins.…”
Section: Discussionmentioning
confidence: 99%